1992
DOI: 10.1136/jcp.45.8.697
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between aleukaemic prodrome of childhood acute lymphoblastic leukaemia and aplastic anaemia.

Abstract: Aims: To document the features of the socalled aplastic presentation of childhood acute lymphoblastic leukaemia (ALL) and to determine whether this prodrome can be distinguished from aplasia.Methods: The peripheral blood and bone marrow appearances of all cases of childhood ALL presenting in one health region of England in 13 years and eight months were reviewed. All cases presenting with cytopenia without circulating blasts and marrow aspirates with no infiltrate of blasts were studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…An increase in bone marrow reticulin may be seen in ND not done hypoplastic AML and hypoplastic MDS but is not increased in AA [17]. Previous studies have also shown increase in reticulin in hypocellular ALL [18,19]; however, our single case of hypocellular ALL did not show increased reticulin, and overall also only one case had increased reticulin fibrosis.…”
Section: Discussionsupporting
confidence: 44%
“…An increase in bone marrow reticulin may be seen in ND not done hypoplastic AML and hypoplastic MDS but is not increased in AA [17]. Previous studies have also shown increase in reticulin in hypocellular ALL [18,19]; however, our single case of hypocellular ALL did not show increased reticulin, and overall also only one case had increased reticulin fibrosis.…”
Section: Discussionsupporting
confidence: 44%
“…Pancytopenic phase(pre-ALL) associated with a hypocellular or normocellular bone marrow may precede the diagnosis of acute lymphoblastic leukemia(ALL). There have been several reports about names to describe this condition, usually in childhood, which include aleukemic prodrome, preleukemic ALL, aplastic presentation of ALL, hypoplastic preleukemia 1 4 ) . There are also several reports 5 7 , 22 ) that present the pathogenesis of pre-ALL and conclude that the pre-leukemic aplasia in childhood is a feature of ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Occasional cases of marrow hypoplasia or aplasia in childhood subsequently evolve into a frankly leukaemic phase, usually acute lymphoblastic leukaemia (ALL) (Melhorn et al, 1970;Breatnach et al, 1981;Saarinen & Wegelius, 1981;Klingemann et al, 1986;Cheng et al, 1987;Reid & Summerfield, 1992;D'Alessio et al, 1993;Liang et al, 1993;Matloub et al, 1993;Sato et al, 1993). In some cases the leukaemia becomes evident after a prolonged period of hypoplasia, but in others the patient appears to recover only to subsequently develop leukaemia.…”
mentioning
confidence: 99%